In Vitro Response of Two Strains of Cordyceps javanica to Six Chemical Pesticides - Ruixia Mao; Xiaoxia Cai; Tengyu Wang; Ziyang Liu; Peixiang Xing; Guisen Zhang; Wenwen Zhou; Hongliang Diao; Ruiyan Ma (Journal of Fungi)
To determine the compatibility of two new biocontrol fungi with common chemical pesticides, this study examined the effects of three insecticides, namely, avermectin, imidacloprid, and acetamiprid, and three fungicides, namely, chlorogenonil, boscalid, and kasugamycin, on the mycelial growth and spore germination of Cordyceps javanica strains IF-1106 and IJ-tg19. The insecticidal effects of mixed insecticides or fungicides with good compatibility with C. javanica IJ-tg19 against Myzus persicae were tested. The results showed that the six chemical pesticides exerted different degrees of inhibition on the mycelial growth of both C. javanica strains, with an obvious dose-dependent effect. The inhibitory effect of chlorothalonil on the mycelial growth of IF-1106 and IJ-tg19 was greater than 75%. Different kinds and concentrations of chemical pesticides had significant effects on spore germination. Among them, acetamiprid had little inhibitory effect on C. javanica spores. Therefore, the two C. javanica strains exhibited good compatibility with the insecticide acetamiprid and had some compatibility with avermectin and imidacloprid. Among the fungicides, the compatibility of the two strains of biocontrol fungi was the best with kasugamycin, followed by boscalid, while their compatibility with chlorothalonil showed the least compatibility. The median lethal time (LT50) of five concentrations of C. javanica IJ-tg19 (1 × 103, 1 × 104, 1 × 105, 1 × 106, and 1 × 107 spore/mL) mixed with acetamiprid against M. persicae were 5.28, 4.56, 3.80, 2.73, and 2.13 days, respectively, and the insecticidal rate was higher than that of fungus treatment alone (5.19, 4.59, 4.05, 3.32, and 2.94 days, respectively) or chemical pesticide treatment (5.36 days). This study provides data support and a theoretical basis for reducing the use of chemical pesticides, improving the efficiency of C. javanica-based insecticides, and optimizing the synergistic use of fungi and chemical pesticides.